Understanding the Role of the Gut Microbiome and Microbial Metabolites in Obesity and Obesity-Associated Metabolic Disorders: Current Evidence and Perspectives - Vallianou, Natalia; Stratigou, Theodora; Christodoulatos, Gerasimos Socrates; Dalamaga, Maria (Current obesity reports, 2019)
Purpose In this review, we summarize current evidence on the gut microbiome and microbial metabolites in relation to obesity and obesity-associated metabolic disorders. Special emphasis is given on mechanisms interconnecting gut microbiome and microbial metabolites with metabolic disorders as well as on potential preventive and therapeutic perspectives with a “bench to bedside” approach. Recent Findings Recent data have highlighted the role of gut dysbiosis in the etiology and pathogenesis of metabolic disorders, including obesity, metabolic syndrome, type 2 diabetes mellitus, and non-alcoholic fatty liver disease. Overall, most studies have demonstrated a reduction in gut microbiome diversity and richness in obese subjects, but there is still much debate on the exact microbial signature of a healthy or an obese gut microbiome. Despite the controversial role of an altered gut microbiome as a cause or consequence of obesity in human studies, numerous animal studies and certain human studies suggest beneficial metabolic effects of certain microbial intestinal metabolites, such as butyrate, that could be used in the prevention and treatment of obesity and its comorbidities. Summary More randomized controlled trials and larger prospective studies including well-defined cohorts as well as a multi-omics approach are warranted to better identify the associations between the gut microbiome, microbial metabolites, and obesity and its metabolic complications.